Immunonutrition support for athletes - Nieman, D. C. (Nutrition Reviews, 2008)
Multiple components of the immune systems in athletes exhibit transient dysfunction after prolonged, heavy exertion. During this "open window" of impaired immunity, pathogens may gain a foothold, increasing infection risk. Nutritional supplements have been studied as countermeasures to exercise-induced immune changes and infection risk. This review focuses on findings from recent exercise-based studies with macro- and micronutrient supplements, and "advanced" immunonutrition supplements including beta-glucan, curcumin, and quercetin. Results from these studies indicate that immunonutrition supplements have the potential to lessen the magnitude of exercise-induced perturbations in immune function and to reduce the risk of upper respiratory tract infections.